Analyzing the Effect of Job Crafting on Person Environment Fit: A Case Study on Uganda Christian University - Grace Mwesigye Ayebare (My University, 2024)
Workers in their different working environments derive ways and modes through which they can attain environment fit and equally organisation fit. This can majorly be done through job crafting. Job crafting is significant because it entails three dimensions which are, relational, cognitive and task crafting. The purpose of this study is to firstly, establish the level of job crafting of the non – teaching staff of Uganda Christian University. Then, to determine the relationship between job crafting and person environment fit. And finally, to determine the state of person environment fit of workers. The research design was cross sectional meaning that the data was collected from one given point in time. Out of all the 58 questionnaires that were sent out to respondents 53 were answered implying a 91% targeted response rate. From the above findings, job crafting and person environment fit were said to be participated on a moderate level which implies that there is given room for improvement in these areas. There was a positive significant relationship between job crafting and person environment fit.